Ultrahigh-Performance Supercritical Fluid Chromatography-Mass Spectrometry in the Clinical Lipidomic Analysis - Peterka, Ondřej; Wolrab, Denise; Jirásko, Robert; Kanásová, Mária; Dolečková, Zuzana; Holčapek, Michal (Methods in molecular biology (Clifton, N.J.), 2025)
Ultrahigh-performance supercritical fluid chromatography-mass spectrometry (UHPSFC/MS) method is optimized for the high-throughput quantitation of lipids in human serum and plasma with an emphasis on robustness and accurate quantitation. Bridged ethylene hybrid (BEH) silica column (100 × 3 mm; 1.7 μm) is used for the separation of 17 nonpolar and polar lipid classes in 4.4 min using the positive ion electrospray ionization mode. The lipid class separation approach in UHPSFC/MS results in the coelution of all lipid species within one lipid class in one chromatographic peak, including two exogenous internal standards (IS) per lipid class, which provides the optimal conditions for robust quantitation. The method was validated according to European Medicines Agency and Food and Drug Administration recommendations. UHPSFC/MS combined with LipidQuant software allows a semiautomated process to determine lipid concentrations with a total run time of only 8 min including column equilibration, which enables the analysis of 160 samples per day.
Keywords: Chromatography, High Pressure Liquid; Humans; Quantitation; lipidomika; Mass spectrometry; lipidy; lidé; Lipidomics; superkritická fluidní chromatografie; Serum; Ultrahigh-performance supercritical fluid chromatography; High-throughput lipidomics; Plasma; Validation; Lipids; Chromatography, Supercritical Fluid; hmotnostní spektrometrie; vysokoúčinná kapalinová chromatografie; Mass Spectrometry